461 Association between temperament and fracture risk in preschool-age children: a case control study. (1st September 2016) - Ryckman, Kandace; Richmond, Sarah A; Anderson, Laura; Birken, Catherine; Parkin, Patricia; Macarthur, Colin; Maguire, Jonathon; Howard, Andrew
Abstract : Background: Approximately half of all children will sustain a fracture during childhood and adolescence. Understanding the factors that place a child at increased risk of fracture is necessary to inform effective injury prevention strategies. Methods: A case-control study design with 128 cases and 426 frequency-matched controls (age and sex) was used to examine the risk of fracture (radiologist diagnosed fracture) in children ages 3–6 years. Cases were recruited from the Hospital for Sick Children Fracture Clinic and controls from the TARGet Kids primary care paediatric network. The Childhood Behaviour Questionnaire (CBQ), a 36-item caregiver response questionnaire was used to assess three temperament factors: surgency (i.e. impulsivity, high activity level); negative affect (i.e. anger, fear, discomfort); and effortful control (i.e. inhibitory control, attentional focusing) as the exposure. Results: Unadjusted logistic models demonstrated no association between children with a fracture and higher scores of surgency (unadjusted OR = 1.06, 95% CI: 0.84, 1.34), negative affect (unadjusted OR = 1.15, 95% CI: 0.93, 1.42) or effortful control (unadjusted OR = 0.80, 95% CI: 0.63, 1.03). Models adjusted for covariates (waist circumference, maternal education, history of fracture, attendance in daycare, amount of time spent in unstructured playtime outdoors, having been breastfed, daily milk and soda consumption), also demonstrated no significant association with surgency (OR = 1.00, 95% CI: 0.78, 1.29), negative affect (OR = 1.09, 95% CI: 0.86, 1.37) and effortful control (OR = 0.80, 95% CI: 0.61, 1.05). Conclusions: Children who are more extraverted, impulsive, aggressive or easily distracted as measured by the CBQ, are not at greater odds of experiencing a fracture, compared to their peers.